Identification and risk assessment of midwife error in the labor using systematic human error reduction and prediction approach - Amin Babaei-Pouya; Zahra Pajohideh; Maryam Feiz Arefi (بهداشت و ایمنی کار, 2021)
Introduction: Labor is one of the most important wards of hospital, where human error is high. Midwifery errors in the maternity ward and in the delivery can be a serious threat to the health of the mother and the infant, resulting in increased treatment costs. Factors affecting human error are diversity in work, high workload, and fatigue. Therefore, this study aimed to evaluate the midwifery errors in the maternity ward using the systematic human error reduction and prediction approach (SHERPA) technique. Material and Methods: This cross-sectional study was conducted in 2019, during which different midwifery tasks were determined in four stages of admitting, pre-labor, delivery, and postpartum. Tasks and sub-tasks were identified using the hierarchical task analysis (HTA) technique and human error was evaluated using the SHERPA technique. Results: The results of the HTA technique identified 19 main tasks, 52 sub-tasks, and 114 activities. After assessing human error risk with the SHERPA technique, the performance was the most frequent type of  error and the highest frequency was related to the undesirable risk level. Conclusion: The errors of the midwifery profession in the hospital’s labor are high-risk and largely critical. Factors such as high workload, time pressure, and fatigue influence the incidence of human error. In order to reduce human error in this area, strategies such as reducing staff workload, developing standard checklists and guidelines are essential to reduce human error in this ward.